A case of haloperidol induced neuroleptic malignant syndrome in postpartum psychosis: a rare case report and review of literature - Meganathan, Jayalakshmi; Thirupathi, Kalaivani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Neuroleptic malignant syndrome (NMS) is a very rare and fatal complication which occurs due to use of Neuroleptic agents in the treatment of psychotic disorders. Neuroleptic drugs are assumed to be safe for both mother and foetus owing to its relative impact on untreated fulminant psychosis. NMS was observed mostly after the use of high potency first generation neuroleptic agents such as haloperidol, fluphenazine, chlorpromazine. NMS is characterised by triad of fever, muscle rigidity and altered mental status. We report a case of 26 years old G2P1L1 pregnant woman presented with abruptio placentae and intrauterine foetal demise at 35 weeks of gestation. During postpartum period, she developed NMS due to usage of haloperidol for postpartum psychosis. In this case we achieved a prompt recovery by using bromocriptine and lorazepam.